2021
DOI: 10.3390/jcm10030432
|View full text |Cite
|
Sign up to set email alerts
|

The Loop Tenodesis Procedure—From Biomechanics to First Clinical Results

Abstract: (1) Introduction: Several surgical therapy options for the treatment of pathologies of the long biceps tendon (LHB) have been established. However, tenotomy, as well as established tenodesis techniques, has disadvantages, such as cosmetic deformities, functional impairments and residual shoulder pain. This study presents the first clinical and structural results of the recently introduced loop tenodesis procedure for the LHB, developed to overcome these issues. (2) Methods: 37 patients (11 women, 26 men, mean … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…With significant advances in arthroscopic instrumentation and implants, a large increase in variations of both tenotomy and tenodesis have been reported. [9][10][11][12][13][14][15] Some authors have demonstrated tenotomy at the biceps anchor can autotenodese in the intra-articular opening of the groove, as the stump base retracts. 16 This implant-free technique may have cost and time-saving benefits; however, a larger proportion of techniques have reported utilisation of implants to secure the tendon.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…With significant advances in arthroscopic instrumentation and implants, a large increase in variations of both tenotomy and tenodesis have been reported. [9][10][11][12][13][14][15] Some authors have demonstrated tenotomy at the biceps anchor can autotenodese in the intra-articular opening of the groove, as the stump base retracts. 16 This implant-free technique may have cost and time-saving benefits; however, a larger proportion of techniques have reported utilisation of implants to secure the tendon.…”
Section: Open Accessmentioning
confidence: 99%
“…This can be either intra-articularly, withing the bicipital groove, or in the subpectoral region of the proximal humerus. With significant advances in arthroscopic instrumentation and implants, a large increase in variations of both tenotomy and tenodesis have been reported 9–15. Some authors have demonstrated tenotomy at the biceps anchor can auto-tenodese in the intra-articular opening of the groove, as the stump base retracts 16.…”
Section: Introductionmentioning
confidence: 99%
“…The study presented by Riedl et al [ 10 ] showed the first clinical and structural results of the recently introduced loop LHB tenodesis procedure. This technique provided good-to-excellent overall clinical results after a short-term follow-up of six months, with an inferior incidence of cosmetic deformities compared to conventional therapy options, such as tenotomy and anchor tenodesis.…”
Section: Introductionmentioning
confidence: 99%